ANALYSIS OF THE PHYSICAL CONDITION OF MEN'S FUTSAL PLAYERS IN MONDA FC IN ACADEMIC YEAR 2023/2024 - Nurdin Nurdin (JOETAL: Journal of Education, Teaching and Learning, 2024)
The Monda FC futsal club is one of the futsal clubs located in Montong Dao Village, Masbagik Utara Baru District, East Lombok Regency, West Nusa Teggara Province. most dominant in playing futsal. For this reason, several things that cause the slow increase in futsal achievements include mastery of techniques, tactics, mental and physical conditions. The aim of this research is to find out the physical condition of the Putra Monda FC Futsal Players in 2023. This research is descriptive research, namely research that is solely aimed at knowing the condition of objects or events without any intention of drawing generally applicable conclusions. The population and sample in this research were 15 Monda FC futsal players. The sampling technique used in this research was Population Study. The instruments for this research are the VO2 Max endurance test, 30 meter running speed test, leg muscle strength test with the Leg and Back Dynamometer. Based on the data analysis above, the highest percentage obtained in each norm is as follows. VO2 Max in the normal category is sufficient at 40%, Speed ​​in the normal category is sufficient at 40%, leg muscle strength in the moderate norm category is 80%.